2016
DOI: 10.1039/c6gc00904b
|View full text |Cite
|
Sign up to set email alerts
|

Downstream integration of microalgae harvesting and cell disruption by means of cationic surfactant-decorated Fe3O4nanoparticles

Abstract: The functionalization of cationic surfactants on Fe3O4 nanoparticles serves two roles at the same time: microalgae harvesting and cell disruption for lipid extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Treatment with NaOH at pH = 12 resulted in 95% recovery for polypropylene/iron oxide nanoparticles, with the recovered magnetic particles retained almost the same microalgae biomass harvesting efficiency as per the newly synthesized ones [ 53 ]. An 80% reusability efficiency of cationic surfactant-decorated iron oxide nanoparticles after microalgae detachment using SDS and sonication has also been reported [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with NaOH at pH = 12 resulted in 95% recovery for polypropylene/iron oxide nanoparticles, with the recovered magnetic particles retained almost the same microalgae biomass harvesting efficiency as per the newly synthesized ones [ 53 ]. An 80% reusability efficiency of cationic surfactant-decorated iron oxide nanoparticles after microalgae detachment using SDS and sonication has also been reported [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…54 No toxic effect induced by the nonamphiphilic cholinium cation is likely due to its less interaction with the lipid membrane of the microalgae, 55 whereas it has been shown that the amphiphilic cations normally have greater interaction toward the cell membrane, leading to higher toxicity. 56 The literature also indicates that small cations are more aggressive than larger cations in inducing the toxicity when the anions are the same. 57 Therefore, alkali cations (Na + and Li + ) are more toxic to living cells than the ammonium cation and the bigger cholinium cation ([Cho] + ).…”
Section: Resultsmentioning
confidence: 99%
“…With the increasing global energy demands and its associated impact on climate have motivated the scientific communities to provide innovative solutions for the development of green, renewable, and economically feasible biofuels. In recent years, microalgae have emerged as a sustainable feedstock for the production of biofuels and high-value carotenoids, due to their inherent abilities including high growth rate, CO 2 sequestration, and effective land utilization, as compared to terrestrial energy crops. However, the production of biofuels and carotenoids from microalgal biomass is still not economically viable, owing to the significant fossil energy inputs required for downstream processes. , For instance, the cost of harvesting microalgal biomass is estimated to be 20–30% of the total production cost. , Moreover, intense energy inputs are required for further downstream processing of biomass involving cell disruption, product extraction and purification. , Hence, the development of an integrated process which concomitantly addresses subsequent downstream step is expected to improve the cost-effectiveness of microalgal products.…”
Section: Introductionmentioning
confidence: 99%